Famili Rhizophoraceae di Hutan Mangrove KKPD Rupat Utara Provinsi Riau Bagian I, Deskripsi Anggota - Syahrial Syahrial; Erlangga Erlangga; Rini Tri Lestari Sembiring; Alfi Syahrin (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2020)
Monitoring the richness of mangrove species is very much needed in formulating management and conservation of mangroves, so a study of the description of the members of the Rhizophoraceae family was conducted in July 2018 in the mangrove forest of the North Rupat KKPD. This study aims to explore the Rhizophoraceae family members who compile the North Rupat KKPD mangrove forest and also aims as a baseline in evaluating the mangrove ecosystem of the North Rupat KKPD in the future. The method used is line transect and cruising. This means that the collected specimens become more complete. A total of 5 species of Rhizophoraceae members have been identified as compilers of the North Rupat KKPD mangrove forest namely Bruguiera gymnorrhiza, B. sexangula, Ceriops tagal, Rhizophora apiculata and R. mucronata.